Guided inquiry learning-based blended learning on chemical equilibrium material to improve senior high school student learning outcomes - Diyah Ayu Ningsih; Dian Novita (Jurnal Pijar Mipa, 2022)
This researchÃÂ aimed to improve student's learning outcomes on chemical equilibrium material through the application of guided inquiry learning usedÃÂ blended learning to determine studentsÃ¢â¬â¢ÃÂ activities and student responses for applied learning. This study uses observation and test methods to collect data and One Group Pretest-Posttest Design to determine an increase in student learning outcomes. The research was conducted at SMA Al-Islam Krian forÃÂ the 2021/2022 academic year. The results showed that implementation of guided inquiry learning based on blended learning was 98.8%, with a very good category. The percentage of student activity is 96%. The learning outcomes obtained by the students showed an increase between the pretest and the posttest, with an average n-gain value of 0.8 in the high category, and from results of paired sample t-test was obtained by the Sig. (2-tailed) 0.000 < 0.005, which means that there is a significant difference. The results of student responses during learning are 96%. This research concludes that guided inquiry learning can improve studentsÃ¢â¬â¢ÃÂ learning outcomes on chemical equilibrium materials.